If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = 4w + 11 Reorder the terms: 63 = 11 + 4w Solving 63 = 11 + 4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4w' to each side of the equation. 63 + -4w = 11 + 4w + -4w Combine like terms: 4w + -4w = 0 63 + -4w = 11 + 0 63 + -4w = 11 Add '-63' to each side of the equation. 63 + -63 + -4w = 11 + -63 Combine like terms: 63 + -63 = 0 0 + -4w = 11 + -63 -4w = 11 + -63 Combine like terms: 11 + -63 = -52 -4w = -52 Divide each side by '-4'. w = 13 Simplifying w = 13
| 2w+10=50 | | -29=-y/3 | | 4(w-5)-3(12-x)=7 | | -y/5=-58 | | 7u=22.4 | | 6.25=5v | | 3x+0=x+4 | | p=13+-2q | | 263-132= | | -58a+90+a=92 | | 16T+7=20y-5 | | 32x^2+4x=0 | | 4=3x-1 | | x/6+2=-6 | | 16x5/3 | | -7a+3-8a=-19 | | 16*5/3 | | 1=5x-4 | | x/6-2=-6 | | 200/10+2e^3x=4 | | 2(x+8)=3(x+7) | | -1/2x^2+2x+6=0 | | F(x)=x^3+5x^2+1 | | 2y+1/6=3y+5/6 | | 2(T-5)=0 | | 3p+4q=38 | | 3=3x-6 | | 87-2=10x+15 | | 2=5x-3 | | 3.85=5.47 | | 3.85=5.4 | | -4x-6=-30 |